Relationship between Parenting Style and Autonomy among Adolescents Studying In Tabriz High Schools - Seyed-Fatemi; Rahmani; Baradaran; Sedaghat (Iran University of Medical Sciences, 2010)
Background and Aim : Parenting style has a range of different outcomes for adolescents, their family relationships, achieving to autonomy, confidence and decision-making capacities. The results of studies about relationship between parenting style and autonomy in adolescents are different and controversial. The aim of the study was to examine the relationship between parenting style and authonomy among adolescents studying in Tabriz high schools.   Material and Method: This was a cross sectional study with multistage cluster sampling of 360 adolescents studying in Tabriz high schools. Questionnaires used in this study were parenting style inventory II, Emotional Autonomy Scale (EAS) and perspective on adolescent decision-making - B. Data were analyzed using SPSS (Version 11).   Results: According to the finding, the majority of adolescents (%39.7) reported authoritative parenting style and there was a statistically significant relationship between parenting style and emotional autonomy (F = 78.6, P<0.05) and behavioral autonomy (F = 6.4, P<0.05).   Conclusion: Regarding the findings, it is suggested that nurses plan education programs about adolescence's characteristic and parenting style outcomes for parents in order to achieve healthy autonomy for the adolescents.